Insights into hydrography modulating population structure of the ocellated icefish (Chionodraco rastrospinosus) in the Bransfield Strait, Antarctica - Zukun Peng; Zhuang Chen; Lingqiao Cheng; Shuhao Ma; Guoping Zhu; Congcong Wang (Estuarine, Coastal and Shelf Science, 2026)

Chemically induced proximity-driven dimerization of split Cas12a enables sensitive rapamycin detection in blood - Zhen Huang; Xiaowen Hu; Yajuan Zhou; Shanshan Zhang; Yao Zhao; Lei Xiong; Xuchun Han; Miaona Liu; Yao Hu; Yizhuo Zhang; Luqin Lv; Qiuxiang Cheng; et al. (Science Bulletin, 2026)

Head-to-head comparison of plasma biomarker assays across platforms for amyloid pathology in a multicenter cohort - Xinyi Lv; Kaiyuan Shen; Qianhua Zhao; Guoping Peng; Huayan Liu; Feng Gao; Xiaodong Pan; Wei Chen; Peilin Lu; Haining Zhang; Shuting Zhang; Mengya Xing; et al. (Science Bulletin, 2026)

The relationship between micro-fragmentation mechanisms and macro-mechanical responses in granite residual soil - Bingxiang Yuan; Xiangwen Deng; Peng Luo; Xueqiang Yang; Jim Shiau; Xiaoyu Bai; Mayao Cheng; Guoping Lei; Junjie Zheng (Transportation Geotechnics, 2026)

The sustained expansion (2011−2022) and abrupt contraction (2023) of the Ross Sea polynyas - Xiaolu Ou; Lingqiao Cheng; Dongming Lin; Guoping Zhu (Journal of Marine Systems, 2026)

Effects of heat treatment on the characteristics of low-molecular-weight oyster peptides (LOPs) W1/O/W2 double emulsions: Physicochemical, interfacial, and rheological properties - Xiaolin Guo; Wanqi Chen; Wenhong Cao; Haisheng Lin; Zhongqin Chen; Jialong Gao; Guoping Zhu; Mingtang Tan; Ming Cheng; Huina Zheng (Food Chemistry, 2026)

Polarity and direction dependence of energetic cross-frontal eddy transport in the Southern Ocean's Pacific sector - Huimin Wang; Lingqiao Cheng; Erik Behrens; Zhuang Chen; Jennifer Devine; Guoping Zhu (Ocean Science, 2026)
Mesoscale eddies play a critical role in mediating meridional transport across the Antarctic Circumpolar Current (ACC), yet the dynamics of cross-frontal eddies (CFEs) and their energy exchanges with frontal jets remain inadequately quantified. This study presents a systematic analysis of CFE characteristics, kinetic energy evolution, and thermohaline transport effects in the Pacific sector of the Southern Ocean, utilizing 23 years (2000–2022) of satellite altimetry and Argo float data. Our results reveal a fundamental polarity- and direction-dependent asymmetry in CFE dynamics. Equatorward-propagating cyclonic eddies (CEs) dominate CFE activity, followed by poleward-moving anticyclonic eddies (AEs). These dominant CFE types exhibit superior energetic characteristics, including significantly higher eddy kinetic energy (EKE) and stronger nonlinearity compared to their counterparts. Complete CFEs experience polarity- and direction-selective energy gains during frontal crossing, with equatorward CEs and poleward AEs extracting energy from eastward frontal jets, while their counterparts lose energy. This energization mechanism has intensified over the past two decades, with both polarity CFEs showing substantial EKE increases that substantially exceed previous basin-scale estimates. Hydrographic analysis demonstrates that CEs and AEs transport distinct water masses across frontal boundaries, creating sharp thermohaline contrasts within interfrontal zones. Our findings establish CFEs as crucial regulators that buffer wind- and warming-induced baroclinicity increases through compensatory heat transport, thereby maintaining the Southern Ocean's thermal equilibrium and modulating the ACC's response to external forcing in a changing climate.

Discovery and implications of the Late Carboniferous Tasensu gabbro–gabbrodiorite–granodiorite–monzogranite bimodal intrusions in Xiwuqi, Inner Mongolia, China - Wenjing Yang; Tianshe Cheng; Xuebin Zhang; Xiangqian He; Guoping Wang; Xujiang Cheng; Linhai Wang; Lijun Guo; Xingfang Duo; Hongsheng Gao (Journal of Volcanology and Geothermal Research, 2026)

Smartphone-assisted curcumin-based fluorescence sensing platform for alcohol content in Chinese liquor via hydrogen bond manipulation - Fang Xu; Longfei Su; Zhenxing Guo; Qiang Cheng; Jiachen Guan; Yuhang Guo; Liqiang Xu; Guoping Sheng (Food Chemistry, 2026)

Development of a photocatalytic mesh system for high-efficiency wastewater purification under real weather conditions: Unveiling hydrodynamic-optical synergy and application potential - Cheng Zhang; Guangqi An; Yunxin Zhu; Zhenghao Wu; Wen Wei; Wenbin Jiang; Guoping Chen; Yingnan Yang (Chemical Engineering Journal, 2026)

Regulation of Melatonin on AQP4 Expression in Brain of SD Newborn Rats with Bilirubin Encephalopathy and Protection Mechanism - Kaige Xue; Xuefeng Cheng; Weijian Qian; Hemant Mistry; Ping Fan; Jiaheng Hu; Chunyan Chen; Lirong Zhang; Parisa Vazirinasab; Juan Huang; Weitian Lu; Jin Xu; et al. (Molecular Neurobiology, 2026)

Dynamically programmable plant-derived scaffold coordinates alveolar bone repair cascade: Phase-adaptive integration from hemostasis to bone remodeling - Yeke Chen; Yumei Ning; Fang Dai; Yuting Yang; Chenjiang He; Kaiqiang Yang; Yichen Hu; Guoping Cheng; Li Song (Chemical Engineering Journal, 2025)

Combined influence of strong winds and warm deep water on the formation of Amundsen Sea Polynya in winter - Mengting Zhuo; Yu Hong; Yuhong Zhang; Jiping Liu; Lingqiao Cheng; Guoping Zhu; Song Hu; Yan Du (Deep Sea Research Part I: Oceanographic Research Papers, 2025)

A dual solar-utilization photocatalytic mesh reactor for efficient harmful algal bloom control in real-world conditions: Performance, mechanism and global deployment - Guangqi An; Cheng Zhang; Yunxin Zhu; Ayaka Yoshii; Hongjian Zhang; Guoping Chen; Yingnan Yang (Chemical Engineering Journal, 2025)

Solar-light-driven inactivation of toxigenic Microcystis by floating photocatalytic mesh system: Insights on physiological mechanism and application - Guangqi An; Cheng Zhang; Yunxin Zhu; Hongjian Zhang; Naoki Kawazoe; Guoping Chen; Yingnan Yang (Water Research, 2025)

Glycine intervention can alleviate imidacloprid-induced spermatogenic damage in rats - Zhihui Zhang; Weilong Cheng; Junsong Xiao; Yixuan Li; Guoping Zhao; Yanbo Wang (Reproductive Toxicology, 2025)

Formation and characterization of theanine-flavonol glycoside adduct and its quantitative analysis during the processing of green tea - Jia-Ping Ke; Guoping Lai; Zisheng Han; Yong Cheng; Mengting Zhu; Liang Zhang (Food Research International, 2025)

Synergy of Fe-modified zeolite and light stimulation on ammonia-stressed anaerobic digestion: Performance, microbial community and metabolic pathway - Zhiyuan Liu; Yunxin Zhu; Mingyuan Sun; Guangqi An; Jingwei Yang; Cheng Zhang; Guoping Chen; Yingnan Yang (Chemical Engineering Journal, 2025)

Transport behavior of Polymeric Methyl Methacrylate nanoplastics in saturated and unsaturated porous media: Combined influence of electrolyte and organic acids - Lihui Tan; Lulu Ding; Ming Wu; Zhou Cheng; Yanru Hao; Guoping Lu (Journal of Environmental Chemical Engineering, 2024)

Genome-wide identification of Aux/IAA gene family members in grape and functional analysis of VaIAA3 in response to cold stress - Shixiong Lu; Min Li; Yongjuan Cheng; Huimin Gou; Lili Che; Guoping Liang; Juan Mao (Plant Cell Reports, 2024)

Impact of diatomit on the transport behavior of unmodified and carboxyl-modified nanoplastics in saturated porous media - Yuheng Wu; Ming Wu; Zhou Cheng; Yanru Hao; Cehui Mo; Qusheng Li; Jianfeng Wu; Jichun Wu; Bill X. Hu; Guoping Lu (Environmental Pollution, 2024)

Development of a sunlight adjustable parabolic trough reactor for 24-hour efficient photocatalytic wastewater treatment - Cheng Zhang; Guangqi An; Yunxin Zhu; Xiang Sun; Guoping Chen; Yingnan Yang (Chemical Engineering Journal, 2024)

Significance of non-DLVO interactions on the co-transport of levofloxacin and titanium dioxide nanoparticles in porous media - Yiqun Cui; Ming Wu; Guoping Lu; Zhou Cheng; Meng Chen; Yanru Hao; Cehui Mo; Qusheng Li; Jianfeng Wu; Jichun Wu; Bill X. Hu (Environmental Pollution, 2024)

Overexpression of VaBAM3 from Vitis amurensis enhances seedling cold tolerance by promoting soluble sugar accumulation and reactive oxygen scavenging - Guoping Liang; Han Wang; Huimin Gou; Min Li; Yongjuan Cheng; Baozhen Zeng; Juan Mao; Baihong Chen (Plant Cell Reports, 2024)

Highly efficient thermal decomposition of AP through intimately encapsulating in 3DOM CoFe2O4 spinel - Desheng Yang; Chaofei Bai; Fengdan Zhu; Chang Liu; Cheng Zhao Tu; Guoping Li; Yunjun Luo; Tianfu Zhang (Chemical Engineering Journal, 2024)

Significance of homogeneous operation in light-assisted fixed-bed bioprocess under ammonia stress: Optimization, long-term operation and metagenomic analysis - Yunxin Zhu; Yujia Chen; Guangqi An; Cheng Zhang; Jingwei Yang; Rongyong Yang; Guoping Chen; Yingnan Yang (Bioresource Technology, 2024)

Why do anaerobes like the light stimulation: Enhanced anaerobic digestion at different wavelengths under ammonia stress - Yunxin Zhu; Guangqi An; Cheng Zhang; Guoping Chen; Yingnan Yang (Chemical Engineering Journal, 2024)

Quantification and visualization of groundwater contamination prevention regionalization based on analytic hierarchy process method (AHP) in Guangdong-Hong Kong-Macao Greater Bay Area, South China - Zhou Cheng; Guoping Lu; Ming Wu; Zhaohui Li; Yirong Deng; Jinzhe Wu; Yanru Hao; Cehui Mo; Qusheng Li; Jianfeng Wu; Jichun Wu; Bill X. Hu (Journal of Hydrology, 2024)

Genome-wide profiling of genetic variations reveals the molecular basis of aluminum stress adaptation in Tibetan wild barley - Cheng-Wei Qiu; Yue Ma; Zi-Feng Gao; Jakkrit Sreesaeng; Shuo Zhang; Wenxing Liu; Imrul Mosaddek Ahmed; Shengguan Cai; Yizhou Wang; Guoping Zhang; Feibo Wu (Journal of Hazardous Materials, 2024)

Quantification of two-site kinetic transport parameters of polystyrene nanoplastics in porous media - Yuheng Wu; Zhou Cheng; Ming Wu; Yanru Hao; Guoping Lu; Cehui Mo; Qusheng Li; Jianfeng Wu; Jichun Wu; Bill X. Hu (Chemosphere, 2023)

Damping, soft, and thermally conductive composite elastomer via introducing bottlebrush chains - Shipeng Rao; Xiangliang Zeng; Xiaxia Cheng; Jianfeng Fan; Dongyi He; Linlin Ren; Guoping Du; Xiaoliang Zeng (Chemical Engineering Journal, 2023)

Important effects of polypropylene on migration of ciprofloxacin in groundwater - Yanna Chen; Cehui Mo; Ming Wu; Yanru Hao; Zhou Cheng; Guoping Lu; Qusheng Li; Bill X. Hu; Jianfeng Wu; Jichun Wu (Journal of Environmental Chemical Engineering, 2023)

Development of a green and efficient photocatalytic mesh microalgae biorefinery (PMMB) system for sustainable biomass conversion under real solar light - Cheng Zhang; Jie Ming; Xiang Sun; Yunxin Zhu; Guangqi An; Guoping Chen; Yingnan Yang (Chemical Engineering Journal, 2023)

Soluble extracellular polymeric substance (SEPS) of histo-blood group antigen (HBGA) expressing bacterium Sphingobacterium sp. SC015 influences the survival and persistence of norovirus on lettuce - Ningbo Liao; Mengxuan Tang; Lili Chen; Peng Tian; Dapeng Wang; Dongqing Cheng; Guoping Wu (Food Microbiology, 2023)

Advanced photocatalytic sterilization for recalcitrant Enterococcus sp. contaminated water by newly developed Z-scheme Bi2WO6 based composites under solar light - Jie Ming; Xiang Sun; Qiansu Ma; Na Liu; Cheng Zhang; Naoki Kawazoe; Guoping Chen; Yingnan Yang (Chemosphere, 2023)

The role of melatonin in tomato stress response, growth and development - Qiaoli Xie; Yu Zhang; Yingxia Cheng; Yanling Tian; Junjie Luo; Zongli Hu; Guoping Chen (Plant Cell Reports, 2022)

Longitudinal virological changes and underlying pathogenesis in hospitalized COVID-19 patients in Guangzhou, China - Zhengtu Li; Yinhu Li; Ruilin Sun; Shaoqiang Li; Lingdan Chen; Yangqing Zhan; Mingzhou Xie; Jiasheng Yang; Yanqun Wang; Airu Zhu; Guoping Gu; Le Yu; et al. (Science China Life Sciences, 2021)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Optimized trio genome sequencing (OTGS) as a first-tier genetic test in critically ill infants: practice in China - Huijun Wang; Yulan Lu; Xinran Dong; Guoping Lu; Guoqiang Cheng; Yanyan Qian; Qi Ni; Ping Zhang; Lin Yang; Bingbing Wu; Wenhao Zhou (Human Genetics, 2020)

Evaluation of spatial distribution of turbulent mixing in the central Pacific - Lingqiao Cheng; Guoping Gao (Journal of Oceanography, 2018)

Genotypic-dependent effects of N fertilizer, glutathione, silicon, zinc, and selenium on proteomic profiles, amino acid contents, and quality of rice genotypes with contrasting grain Cd accumulation - Fangbin Cao; Manman Fu; Runfeng Wang; Wangda Cheng; Guoping Zhang; Feibo Wu (Functional & Integrative Genomics, 2017)

QTL analysis of three flower-related traits based on an interspecific genetic map of Luffa - Junjie Cui; Jiaowen Cheng; Guoping Wang; Xin Tang; Zhiming Wu; Mingbao Lin; Lianfang Li; Kailin Hu (Euphytica, 2015)

Alumina surfaces with nanoscale topography reduce attachment and biofilm formation by Escherichia coli and Listeria spp. - Guoping Feng; Yifan Cheng; Shu-Yi Wang; Lillian C. Hsu; Yazmin Feliz; Diana A. Borca-Tasciuc; Randy W. Worobo; Carmen I. Moraru (Biofouling, 2014)

Modulation of Exogenous Glutathione in Phytochelatins and Photosynthetic Performance Against Cd Stress in the Two Rice Genotypes Differing in Cd Tolerance - Yue Cai; Fangbin Cao; Wangda Cheng; Guoping Zhang; Feibo Wu (Biological Trace Element Research, 2011)